From west to east, working as a woman in foreign service - Åkerblom, Ida; Rolenc, Jan Martin, 1980-; Zemanová, Michaela; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2022)
This master's thesis attempts to answer the research question "What challenges do Western women working in foreign service in majority-Muslim countries perceive and confront?". This is completed by sampling a group of women via five semi-structured interviews originating from Sweden, Finland, and Czech Republic and have been stationed in Iran, Egypt, Pakistan, and Algeria. The interviews are further discussed, analyzed and similarities with previous literature and theoretical framework are drawn, from where recommendations are made.
Vedoucí práce: Jan Martin Rolenc
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2022
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2022
Způsob přístupu: Internet
Keywords: international and diplomatic studies [obor dipl. práce]; diplomové práce; master's theses